A 19 year old with heavy vaginal bleeding; unlikely diagnosis of uterine carcinsarcoma - Atkinson, Andrew L.; Osial, Paulina; Manuel, Michael (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Uterine carcinosarcoma is a rare malignancy that has a high recurrence rate after treatment with very poor long term prognosis. Women are diagnosed usually over the age of 50, with most cases occurring between the sixth and seventh decade of life. We present a rare case of uterine carcinosarcoma diagnosed a nineteen year old after having a dilation and curettage for heavy vaginal bleeding. The patient went on to have a total abdominal hysterectomy with transposition of the ovaries as well as adjuvant treatment with chemotherapy.